Family Guide to the National Insurance Scheme ([London] : His Majesty's Stationery Office, 1948)
1948 1948 1940s 32 pages : illustrations The Grant is £20 when an adult dies, and a smaller sum when a child dies. No Grants are payable for deaths before 5th July 1949, or for deaths of persons already over pension age (65 for men, 60 for women) on 5th July 1948, or of children born before 5th July 1948 if they die before they are ten years old. Reduced Grants will be paid for the deaths of people who on 5th July 1948, are over 55 (men) or over 50 (women). PART FOUR Industrial Injury Benefits Explained 48. What does Industrial Injury Insurance do? It takes the place of the Workmen's Compensation Acts and provides insurance against being unable to work, or being disabled, or losing life, because of accident at work or certain industrial diseases. It covers everyone in Class 1 of the National Insurance Scheme. Those in Class 2 and Class 3 are not included. 49. Are there any Contribution Conditions? No: the right to benefit does not depend on the number of contributions paid. 50. When is Benefit Payable? Benefit is payable when an insured person either suffers personal injury by accident "arising out of and in the course of his employment," or contracts one of the prescribed diseases due to the nature of his employment. (See Special Leaflet N.I.2 from your local National Insurance Office.) 27 345/3/2/10